The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/bdd.498
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol is efficiently glucuronidated by UDP‐glucuronosyltransferases in the human gastrointestinal tract and in Caco‐2 cells

Abstract: Resveratrol (3, 5, 4'-trihydroxy-trans-stilbene), a natural polyphenol present in grapes and peanuts, has been reported to exert a variety of potentially therapeutic effects. The aim of this study was to determine the contribution of the gastrointestinal (GI) tract to the glucuronidation of this compound and its cis-isomer, which also occurs naturally. For this purpose, glucuronidation of the two resveratrol isomers was investigated in human microsomes prepared from: stomach, duodenum, four segments of the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 32 publications
10
49
1
Order By: Relevance
“…3B depicts the results obtained with UGT1A6-genotyped livers. cis-R3G was formed to a greater extent than cis-R4ЈG, as has been previously reported (Aumont et al, 2001;Sabolovic et al, 2006). The velocities in UGT1A6 *1/*2 and *2/*2 livers were significantly different ( p Ͻ 0.05) from that in UGT1A6 *1/*1 livers for the formation of cis-R3G.…”
Section: Kinetic Parameter Estimates For the Formation Of Cis-resverasupporting
confidence: 81%
See 2 more Smart Citations
“…3B depicts the results obtained with UGT1A6-genotyped livers. cis-R3G was formed to a greater extent than cis-R4ЈG, as has been previously reported (Aumont et al, 2001;Sabolovic et al, 2006). The velocities in UGT1A6 *1/*2 and *2/*2 livers were significantly different ( p Ͻ 0.05) from that in UGT1A6 *1/*1 livers for the formation of cis-R3G.…”
Section: Kinetic Parameter Estimates For the Formation Of Cis-resverasupporting
confidence: 81%
“…cis-RES glucuronidation was studied in UGT1A6 recombinant Supersomes and other protein sources to determine and characterize kinetic profile(s) for the formation of the two known metabolitescis-R3G and cis-R4ЈG (Aumont et al, 2001;Sabolovic et al, 2006). Only cis-R3G was formed at the concentration range studied (0 -2000 M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…132 In yet another vitro study using Caco-2 cells, resveratrol 3-sulfate and resveratrol 3-glucoronide were the major phase II biotransformation products. 133 These in vitro studies confirm that resveratrol is fairly well absorbed and metabolized in the small intestine.…”
Section: Resveratrol: Bioavailability Tissue Distribution and Pharmamentioning
confidence: 54%
“…14,15) Therefore, glucuronidation of drugs in the intestine has been studied using Caco-2 cells. [16][17][18] In contrast, the Caco-2 cell line had not been employed to examine the intestinal metabolism of CYP3A4 substrates due to its lack of CYP3A4 expression. Recently, however, it has been reported that CYP3A4 in Caco-2 cells is induced by 1a,25-dihydroxyvitamin D 3 (VD 3 ).…”
mentioning
confidence: 99%